The yield spread puzzle and the information content of SPF forecasts - Kajal Lahiri; George Monokroussos; Yongchen Zhao (Center for Economic Studies and ifo Institute (CESifo), 2012)
While the yield spread has long been recognized as a good predictor of recessions, it seems to have been largely overlooked by professional forecasters. We examine this puzzle, established by Rudebusch and Williams (2009), in a data-rich environment including not just the yield spread but many other predictors as well. We confirm the puzzle in this context by examining the contributions of both the SPF forecasts and the yield spread in predicting recessions, and by examining the information content of SPF forecasts directly. Furthermore, we take the first step towards a possible resolution of this puzzle by recognizing the heterogeneity across professional forecasters.
Keywords: C53; E43; E47; 330; probability forecasts; yield spread; real-time data; Konjunkturprognose; Prognoseverfahren; Sachverständige; Rendite; Zinsstruktur; Schätzung; USA